Deciphering oxidative stress contributions in vestibular schwannoma: A bioinformatics approach to novel therapeutic pathways - Yubin Xue; Mingyue Wang; Hongwei Ma (PLoS ONE, 2025)
Background Vestibular schwannoma (VS) is a benign tumor originating from Schwann cells, and its molecular pathogenesis remains poorly understood. Increasing evidence suggests oxidative stress (OS) plays a critical role in tumor development, but its involvement in VS is largely unexplored. Methods We analyzed two GEO transcriptomic datasets (GSE54934 and GSE56597) to identify oxidative stress-related differentially expressed genes (OSRDEGs). Functional enrichment, protein–protein interaction (PPI) network construction, hub gene identification, and immune infiltration analyses were performed to uncover potential molecular mechanisms. Results Fifteen OSRDEGs were identified, and nine hub genes (IL6, CYBB, CAV1, EGFR, SELE, IL18, CDKN2A, ADIPOQ, CDH2) were screened. Enrichment analysis indicated that these genes are mainly involved in apoptosis, reactive oxygen species regulation, and immune-related pathways. Moreover, immune infiltration analysis revealed significant differences in CD8 + T cells and macrophage populations between VS and control tissues. Conclusions Our study suggests that oxidative stress may contribute to VS progression by influencing immune responses and signaling pathways. These findings provide new insights into the molecular basis of VS and may guide future experimental and therapeutic investigations.